Using Android Technology for Early Detection of Stunting in Toddlers in Krembangan Selatan - Ridha Makruf, Muhammad; Pudji, Andjar; Nugraha, Priyambada Cahya; Wisana, I Dewa Gede Hari (Frontiers in Community Service and Empowerment, 2025)
Stunting is a long-term health problem that mainly impacts the growth and development of young children, particularly in residential areas like Kelurahan Krembangan Selatan, Surabaya. A significant obstacle in preventing stunting is finding a practical way to assess children's nutritional status. This community study aims to raise awareness and educate people about the use of Android-based tools for monitoring body mass index (BMI) and basal metabolic rate (BMR) as innovative methods for detecting stunting risk. The device, tested on 16 infants, enables users to submit detailed data to a web platform for further analysis. Findings reveal that this tool simplifies processes, accelerates data handling, and provides quicker access to up-to-date information, thereby reducing the burden of manual tasks. Results also show that most infants have healthy growth, although some individuals may need more time to understand the benefits. In general, this web-based solution greatly improves the precision and speed of stunting detection and could be widely adopted in areas with limited healthcare infrastructure. However, the study is limited by its small sample size and limited assessment of result length. Future research should focus on a broader population and integrating this tool into larger healthcare systems. This innovation facilitates timely and accurate monitoring of young children's health. The hope is that it will become part of regular posyandu services to help strengthen the stunting prevention program across the Puskesmas Krembangan Selatan area.